Steady-State and Dynamic Modeling of Intermediate-Temperature Protonic Ceramic Fuel Cells. Issue 10 (28th June 2019) - Albrecht, K. J.; Dubois, A.; Ferguson, K.; Duan, C.; O'Hayre, R. P.; Braun, R. J.
Abstract : Protonic ceramic fuel cells (PCFC) have emerged as a promising candidate for distributed power generation. The reduced temperature cells (∼500°C) have the potential to enable faster start-up times, longer life, and lower cost materials compared to oxygen-ion conducting fuel cells. However, the modeling of PCFCs is confounded by several challenges, including estimating open circuit conditions for mixed charged conductors. Here we present the development of a PCFC computational framework for a predictive cell-level, interface charge transfer model capturing mixed conduction, as well as transients. Our approach employs a 1-D heterogeneous channel-level modeling strategy that resolves fuel depletion and flow configuration effects along the length of the channel and is coupled to a semi-empirical electrochemical model. The model is formulated in such a way that allows for easy integration of modeling parameters extracted from button cell experiments and performance scale-up to cell-level predictions. Humidified methane-fueled simulations display power densities above 0.125 W-cm −2 at 500°C, 0.15 A cm −2, and 80% fuel utilization cell conditions. Dynamic simulations indicate that the lower power density PCFCs (relative to solid oxide fuel cells) result in relatively slow thermal transients that could potentially dampen harmful effects of current-based fuel control during load-following operation.